2021
DOI: 10.1136/neurintsurg-2020-017089
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of vertebral artery dissecting aneurysms : a 20-year institutional experience

Abstract: BackgroundThe ideal treatment for unruptured vertebral artery dissecting aneurysms (VADAs) and ruptured dominant VADAs remains controversial. We report our experience in the management and endovascular treatment of patients with VADAs.MethodsPatients treated endovascularly for intradural VADAs at a single institution from January 1, 1999, to December 31, 2019, were retrospectively reviewed. Primary neurological outcomes were assessed using modified Rankin Scale (mRS) scores, with mRS >2 considered a poor ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…In a study of multiple stent therapy in patients with VAFAs, Chung et al ( 17 ) reported a 100% success rate without treatment-related complications; in their literature review, they found a 3.6% complication rate in patients treated using multiple stents. Catapano et al ( 24 ) also reported success and no complications with the use of flow diverter stents in patients with vertebral artery dissecting aneurysms. In contrast, Kallmes et al ( 25 ) reported a 7.3% incidence of ischemic stroke in patients with posterior circulation aneurysms who underwent placement of a flow diverter stent (Pipeline embolization device).…”
Section: Discussionmentioning
confidence: 95%
“…In a study of multiple stent therapy in patients with VAFAs, Chung et al ( 17 ) reported a 100% success rate without treatment-related complications; in their literature review, they found a 3.6% complication rate in patients treated using multiple stents. Catapano et al ( 24 ) also reported success and no complications with the use of flow diverter stents in patients with vertebral artery dissecting aneurysms. In contrast, Kallmes et al ( 25 ) reported a 7.3% incidence of ischemic stroke in patients with posterior circulation aneurysms who underwent placement of a flow diverter stent (Pipeline embolization device).…”
Section: Discussionmentioning
confidence: 95%
“…The rates of procedural complications (8%) and retreatment (13%) were significantly higher with stent/coil treatment than with vessel sacrifice or flow diversion devices. 2 …”
Section: Discussionmentioning
confidence: 99%
“…Owing to the evolution of endovascular techniques and devices and the higher rates of microsurgical complications, vertebral artery (VA) and posterior inferior cerebellar artery (PICA) aneurysms are predominantly treated with endovascular procedures. 1 , 2 , 3 , 4 , 5 , 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…With the development of treatment concept, flow diverting devices represented by the pipeline embolization device (PED, Medtronic, Irvine, California) have become an important alternative to conventional coil embolization in the treatment of unruptured intracranial aneurysms. [1][2][3][4][5][6][7][8][9] For large and giant aneurysms, the 5-year cure rate is more than 95% with the flow diverting device. [10] Recently, different flow diverting devices have been developed including the PED, the Surpass stent (Stryker Neurovascular, Kalamazoo, MI), the Flow-Redirection Endoluminal Device (MicorVention, Tustin, CA), and the Silk flow diverter (Balt Extrusion, Montmorency, France), which have been increasingly applied in over 50 countries.…”
Section: Introductionmentioning
confidence: 99%